Effect of Ar pressure on grain size of magnetron sputter-deposited Cu thin films - Chan, K.Y.; Teo, B.S. (INST ENGINEERING TECHNOLOGY-IET, 2007)
Copper (Cu) thin films with thicknesses ranging from 300 to 425 nm were prepared at various argon (Ar) pressures on p-type silicon substrates by direct current magnetron sputtering deposition. X-ray diffraction (XRD) and Karl Suss four-point probe were employed to study the film crystallinity and conductivity, respectively, as a function of Ar pressure in the deposition process. Detailed analysis on the XRD patterns shows that low Ar pressure enhances the Cu film crystallinity with larger grain size, which was deduced using Scherrer's formula. The behaviour of the electrical property of the Cu films complies with the trend of the grain size with Ar pressure, in which the film conductivity decreases with increasing Ar pressure. The authors attribute these phenomena to the degraded surface diffusion mechanism of the adatom on the growing surface, with increasing Ar pressure during the sputtering deposition process.